2001
DOI: 10.1002/1099-0690(200102)2001:4<647::aid-ejoc647>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

First Enantioselective Total Synthesis of Both (+)- and (−)-Metachromin A

Abstract: The antineoplastic agent (−)‐metachromin A (1) from Hippospongia metachromia has been synthesized in enantiomerically pure form in 13% overall yield. A general convergent synthetic strategy for different metachromins using a 2‐alkyloxy‐3‐sulfonyl‐1,3‐oxazolidine as a chiral dithienium equivalent is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…[29] Over the course of developing conditions for this transformation, Hoppe and coworkers found that a pseudoephedrine-derived oxazolidine ( 12 ) undergoes reaction with silyl enol ethers to afford α-substituted ketones. Remarkably, silyl enol ethers bearing aromatic substituents are alkylated with the opposite sense of diastereoselectivity relative to simpler aliphatic analogs ( 14 vs. 15, Scheme 5).…”
Section: Substrate–substrate Cation–π Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Over the course of developing conditions for this transformation, Hoppe and coworkers found that a pseudoephedrine-derived oxazolidine ( 12 ) undergoes reaction with silyl enol ethers to afford α-substituted ketones. Remarkably, silyl enol ethers bearing aromatic substituents are alkylated with the opposite sense of diastereoselectivity relative to simpler aliphatic analogs ( 14 vs. 15, Scheme 5).…”
Section: Substrate–substrate Cation–π Interactionsmentioning
confidence: 99%
“…Remarkably, silyl enol ethers bearing aromatic substituents are alkylated with the opposite sense of diastereoselectivity relative to simpler aliphatic analogs ( 14 vs. 15, Scheme 5). [29e] …”
Section: Substrate–substrate Cation–π Interactionsmentioning
confidence: 99%
“…In this particular example, desulfurization with RANEY s nickel led to reduction and isomerization of the carbon-carbon double bonds, Birch conditions gave either mono-desulfurization at À78 1C or reduction of the aromatic ring at higher temperature and preparation of the hydrazones led to degradation. 111…”
Section: Scheme 33mentioning
confidence: 99%
“…It could be inferred, based on the previous data concerning structure-activity, that in this first screening the presence of the hydroquinonic segment would initially generate oxidative stress on the tested cells causing a significant raise on cell death related the presence of allyl alcohol and free hydroxyl moieties on the terpenic decalin rings, which possess a lower activity than diterpenhydroquinones had previously shown. Also the highest apoptotic effect of the compounds, which contain in their structure the hydroquinone segment, would promote the cytotoxic ability of the terpenic decalins due, probably, to the conjugated system present in the compounds 1 – 3 , analogous to the metachromins A-H series [ 29 ] which has shown a range of cytotoxic activities against murine leukemia cells and human epidermoid carcinoma cells [ 30 ].…”
Section: Resultsmentioning
confidence: 99%